Improving health literacy with mumps, measles and rubella (MMR) vaccination: comparison of the readability of MMR patient-facing literature and MMR scientific abstracts - Tina Downey; Beverley C. Millar; John E. Moore (SAGE Publishing, 2022)
Background: Historically, there have been many factors that have influenced mumps, measles and rubella (MMR) vaccine uptake, including media bias, social/economic determinants, parental education level, deprivation and concerns over vaccine safety. Readability metrics through online tools are now emerging as a means for healthcare professionals to determine the readability of patient-facing vaccine information. The aim of this study was to examine the readability of patient-facing materials describing MMR vaccination, through employment of nine readability and text parameter metrics, and to compare these with MMR vaccination literature for healthcare professionals and scientific abstracts relating to MMR vaccination. Materials and methods: The subscription-based online Readable program (readable.com) was used to determine nine readability indices using various readability formulae: Established readability metrics ( n  = 5) (Flesch-Kinkaid Grade Level, Gunning Fog Index, SMOG Index, Flesch Reading Ease and New Dale-Chall Score), as well as Text parameters ( n  = 4) (sentence count, word count, number of words per sentence, number of syllables per word) with 47 MMR vaccination texts [patient-facing literature ( n  = 22); healthcare professional-focused literature ( n  = 8); scientific abstracts ( n  = 17)]. Results: Patient-facing vaccination literature had a Flesch Reading Ease score of 58.4 and a Flesch-Kincaid Grade Level of 8.1, in comparison with poorer readability scores for healthcare professional literature of 30.7 and 12.6, respectively. MMR scientific abstracts had the poorest readability (24.0 and 14.8, respectively). Sentence structure was also considered, where better readability metrics were correlated with significantly lower number of words per sentence and less syllables per word. Conclusion: Use of these readability tools enables the author to ensure their research is more readable to the lay audience. Patient co-production initiatives would help to ensure that not only can the target audience read the literature, but that they understand the content. Increased patient-centric focus groups would give better insights into reasons for MMR-associated vaccine hesitation and vaccine refusal.